Checklist of Colombian cockroaches (Dictyoptera, Blattaria) (2008)
ABSTRACT: This paper reviews the current state of knowledge about Blattaria for Colombia. Generalities on the suborder are presented and the species present in Colombia are catalogued. This study was made based on the literature and analysis of the various Colombian collections. The species listing obtained is made up of four families with 15 subfamilies, 62 genera and 133 species that account for 3.1% of the 4,330 species recognized worldwide. Moreover, an altitudinal range is given as well as distribution data for Colombia’s biogeographical regions and departments. Some notes are made on the distribution for each region and on collection methods.